Rancang Bangun Desain Bilah Turbin Angin Taperless Sumbu Horizontal 3 Sudu Menggunakan Material Kayu Mahoni: Studi Eksperimen Sistem Pengereman Elektrik Dynamic Braking dan Performa di Pantai Asmara Jember - Sulaiman, Zainal Muttaqien; Poma, Yoniva Nandarista; Fredyansyah, Maulana Alfi; Merican, Marcelino Ricky; Puspitasari, Vita Ayu; Zainuri, Muhammad (P3M Politeknik Negeri Jember, 2025)
Wind turbines are one of the environmentally friendly conversion tools with one of the main components being blades. Jember is one of the districts of East Java. The average wind speed in Indonesia is relatively low ranging from 3 m/s to 5 m/s. The potential for wind in Indonesia is available almost all year round, so there is a possibility of developing technology to utilize this energy with some previous limitations. Windmill modifications need to be made that are adapted to low wind speed conditions to be able to produce optimal electrical energy. Therefore, a design of HAWT (Horizontal Axis Wind Turbine) blades using mahogany wood material was made by testing the current, voltage, and wind speed system at Asmara Beach, Jember. This study aims to design and evaluate the performance of a taperless bladed wind turbine made from mahogany wood as an alternative environmentally friendly material. The turbine design is optimized through numerical simulation to achieve maximum efficiency. The results show that wind turbines made from mahogany wood have potential as a promising source of renewable energy, especially in areas with moderate wind speeds.